Study on graduates of Diploma In Public Administration (DPA) OF UiTM, Samarahan Campus from 1998 to 2000 / Camelia Roman … [et.al.]. - Roman, Camelia; Pa'ee, Dyzamela; Barieng, Diana Sophia; Abdillah, Siti Noramiza; Justin Jagin, Laura Kristi (2002)
Our study is about trace study on graduates of Diploma in Public Administration (DPA) UiTM Samarahan campus from 1998-2000. For the study, we have use the questionnaire method and it has been distributed to a sample of 120 respondents who are DPA's graduates of UiTM Samarahan campus. The sample is randomly selected from the Sarawak area only. We try to identify what are the weaknesses and the strengths of the SSE DPA program besides analyzing the achievement of the DPA's graduates after the completion of their diploma. From our study, we found that most of the respondents continued their study to higher qualification that is to the degree level. Most of them claim that the DPA program is a good program and it should maintain the performance by producing more DPA graduates.